Redescription of Astyanax stenohalinus Messner, 1962 (Characiformes: Characidae), a poorly known species from Argentina and Uruguay - Almirón, Adriana E.; Casciotta, Jorge R.; de Las M. Azpelicueta, María; Loureiro, Marcelo (Zootaxa, 2010)
Astyanax stenohalinus Messner, 1962 is redescribed based on type material and new specimens collected in many localities of Argentina and Uruguay. This species is distinguished by a combination of the following characters: possession of hooks in all fins of males, teeth not expanded distally, two or three maxillary teeth, 37–39 perforated scales in the lateral series, 25–30 branched anal-fin rays, and anal-fin origin located before a vertical through last dorsal-fin ray insertions.